Bacterial community dynamics during ensiling of perennial ryegrass at two compaction levels monitored by terminal restriction fragment length polymorphism - Graf, K.; Ulrich, A.; Idler, C.; Klocke, M. (Journal of applied microbiology, 2016)
Aims The purpose of this study was to investigate the effects of compaction and air infiltration on the bacterial community structure during the fermentation process and the aerobic exposure phase of grass silage. Methods and Results Perennial ryegrass was ensiled at laboratory scale in a high‐density (HD) and low‐density (LD) compaction variant. Silages were exposed to air, and degradation was monitored by analysing temperature changes within the silage. Fermentation dynamics were examined using chemical analysis and terminal restriction fragment length polymorphism (TRFLP) analysis of the 16S rRNA gene supported by cloning and sequencing of representative samples. Dominant Lactobacillus species in HD silages remained largely unchanged during aerobic exposure. LD silages revealed fundamental changes in the bacterial community structure when exposed to air. After 4 days aerobic storage, only 23% of the primary silage community remained and mainly opportunistic Bacillus species proliferated. Conclusion The ensiling of ryegrass is a very dynamic microbial process. Aerobic spoilage was limited to the LD silages, marked by a complete change towards a Bacillus‐dominated community. Significance and Impact of the Study The TRFLP analysis supported by the identification of terminal restriction fragments, revealed novel insights into the dynamics of the bacterial community during ensiling, and at aerobic spoilage conditions.